Agricultural Robotics : The Future of Robotic Agriculture /: The Future of Robotic Agriculture. ([2018]) - Duckett, Tom; (Professor of agri-food technology), Pearson, Simon; Blackmore, Simon; Grieve, Bruce
No abstract available